Self-harm and suicidality among LGBTIQ people: a systematic review and meta-analysis. (19th May 2022) - Marchi, Mattia; Arcolin, Elisa; Fiore, Gianluca; Travascio, Antonio; Uberti, Daniele; Amaddeo, Francesco; Converti, Manlio; Fiorillo, Andrea; Mirandola, Massimo; Pinna, Federica; Ventriglio, Antonio; Galeazzi, Gian Maria; et al.
Abstract: Research evidence has consistently documented a higher risk of suicidality in the Lesbian, Gay, Bisexual, Transgender, Intersex, and Queer (LGBTIQ) population. This systematic review and meta-analysis aimed to report a detailed description of research data regarding the risk of Attempted Suicide (SA), Suicide Ideation (SI), and Non-Suicidal Self-Injury (NSSI) behaviours for LGBTIQ people and their subgroups. Medline, Scopus, PsycINFO, and EMBASE were searched for studies reporting a comparative estimation of SA, SI, and NSSI rates among LGBTIQ population and the general population (i.e. heterosexual/cisgender), without restrictions on participants' age and setting for the enrolment. Pooled analyses were based on odds ratios (ORs, with 95% CIs), estimated through inverse variance models with random effects. Fifty studies were selected for the quantitative synthesis and included fifty samples involving 3.735.601 controls and 87.252 LGBTIQ people. LGBTIQ people reported an increased risk of SA (OR:4.36[95%CI:3.32;5.71]), SI (OR:3.76[95%CI:3.02;4.69]), and NSSI (OR:4.24[95%CI:3.23;5.55]). Among LGBTIQ subgroups, the Bisexual group has shown the highest risk of suicidality (SA, OR:6.71; SI, OR:5.04; NSSI, OR: 5.03), followed by the Lesbian-Gay for attempted suicide (SA, OR:6.03), and the Transgender-Intersex-Queer for suicide ideation and non-suicidal self-injury (SI and NSSI, OR:3.42). The quality of the evidence ranged from low to moderate. Our findings have shown that LGBTIQ people report a higher risk of suicidality compared with their cisgender/heterosexual peers. This evidence may contribute to the public awareness on LGBTQI mental health needs and suggest supportive strategies as well as preventive interventions (e.g. supportive programs, counselling, and destigmatizing efforts) as parts of a tailored health-care planning aimed to reduce psychiatric morbidity and mortality in this at-risk population.